Pathogenic variation underlying rare diseases in an Arab population: Implications for screening programs - Ruchi Jain; Sami Bizzari; Sathishkumar Ramaswamy; Khaleem F. Hasham; Shruti Sinha; Ikram Chekroun; Fatma Rabea; Eman Abuijlan; Maha El Naofal; Massomeh Sheikh Hassani; Shruti Shenbagam; Alan Taylor; et al. (Genetics in Medicine Open)
Purpose: Genetic variation underlying rare diseases in Arab populations is poorly understood limiting effective carrier screening for recessive disorders, which are prevalent because of high consanguineous rates. Methods: Using the American College of Medical Genetics and Genomics/Association for Molecular Pathology guidelines, we curated pathogenic (P) and likely pathogenic (LP) variants in 1333 Arab Emirati families (346 internal cohort and 987 from the literature). We also analyzed P/LP variants in 1194 Emirati exomes, calculated allele frequencies, and estimated carrier rates for the associated recessive conditions. Results: Among the 1333 families, 1060 had 701 variants meeting the American College of Medical Genetics and Genomics/Association for Molecular Pathology criteria for pathogenicity, with 52% and 30% being absent from the Genome Aggregation Database and ClinVar databases, respectively. Independently, we determined the frequency of P/LP variants in 1194 Emirati exomes, as well as cumulative gene-disease carrier rates. The CYP21A2 gene (HGNC:2600) showed the highest carrier rate (10.6%) followed by HBB (HGNC:4827) (9.6%), MEFV (HGNC:6998) (5.9%), and ABCA4 (HGNC:34) (4.3%). Using a provisional gene list for carrier screening, based on our analysis, we estimated an at-risk couples rate of 4% to 21%, which varies across different screening panels recommended in other populations. Conclusion: Our findings emphasize the necessity of identifying prevalent diseases in underrepresented populations to develop effective and equitable preventive public health measures, including premarital screening programs.